Genomic investigation of clinically significant coagulase-negative staphylococci. Issue 3 (11th March 2021) - Cole, Kevin; Atkins, Bridget; Llewelyn, Martin; Paul, John
Abstract : Introduction. Coagulase-negative staphylococci have been recognized both as emerging pathogens and contaminants of clinical samples. High-resolution genomic investigation may provide insights into their clinical significance. Aims. To review the literature regarding coagulase-negative staphylococcal infection and the utility of genomic methods to aid diagnosis and management, and to identify promising areas for future research. Methodology. We searched Google Scholar with the terms ( Staphylococcus ) AND (sequencing OR (infection)). We prioritized papers that addressed coagulase-negative staphylococci, genomic analysis, or infection. Results. A number of studies have investigated specimen-related, phenotypic and genetic factors associated with colonization, infection and virulence, but diagnosis remains problematic. Conclusion. Genomic investigation provides insights into the genetic diversity and natural history of colonization and infection. Such information allows the development of new methodologies to identify and compare relatedness and predict antimicrobial resistance. Future clinical studies that employ suitable sampling frames coupled with the application of high-resolution whole-genome sequencing may aid the development of more discriminatory diagnostic approaches to coagulase-staphylococcal infection.